The Ideal Law State Concept in Indonesia; The Reality and The Solution - Juanda, Ogiandhafiz; Juanda (Dinasti Research, 2023)
The rule of law concept that has developed in Indonesia is a modern rule of law concept that has a distinctive feature compared to the concept of a rule of law state that developed before. However, in the development process, it is difficult to escape from the sparks of thinking about the concepts of